2013
DOI: 10.1038/ejcn.2013.208
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth does not associate with cognitive development in Indian school-age children

Abstract: Evidently, stunting remains associated with cognitive ability in school-age children; however, the reversal of these effects in this age group may be quite difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…An Indian study also reported poor performance of malnourished children in the age groups of 5–7 and 8–10 years, on tests of attention, working memory, learning and memory, and visuospatial ability (Kar et al, ). The cognitive scores remained unchanged even with a nutritional supplementation for 6 months to both stunted and nonstunted children in an Indian study (Sokolovic et al, ). One Bangladeshi study conducted by Tarleton and colleagues assessed cognitive function of school children aged 6–9 years, living in a slum of Mirpur.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An Indian study also reported poor performance of malnourished children in the age groups of 5–7 and 8–10 years, on tests of attention, working memory, learning and memory, and visuospatial ability (Kar et al, ). The cognitive scores remained unchanged even with a nutritional supplementation for 6 months to both stunted and nonstunted children in an Indian study (Sokolovic et al, ). One Bangladeshi study conducted by Tarleton and colleagues assessed cognitive function of school children aged 6–9 years, living in a slum of Mirpur.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, stunted children have vocabulary deficits and other deficiencies in school performance and intelligence (Crookston et al, ). The deleterious long‐term effect of stunting was also evident in a recent Indian study that reported that persistently stunted children aged 6 and 12 years had poorer performance on short‐term memory, cognitive speed, retrieval ability, and visuospatial ability tests (Sokolovic et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…Nutritional interventions have been shown to be most effective at minimizing the impact of insults to cognitive development when administered during the first 2 years of life (Ip et al, 2017). However, there is vast heterogeneity in this domain, since other studies concluded that improving nutritional intake does not result in better cognitive performance (Sokolovic et al, 2014). Perkins et al (2017) argue that these discrepant findings could be due to heterogeneity in the type of intervention administered, child sex and family demographics.…”
Section: Association Between Cognitive Development and Growthmentioning
confidence: 99%
“…Stunting in early life is associated with short-term and long-term consequences. Stunting may hamper the structural and functional development of the brain, resulting in delayed cognitive function development or permanent cognitive impairment which may lead to poor academic achievement and low economic productivity (3)(4)(5) . Childhood stunting is directly related to short adult stature and may have intergenerational effects.…”
mentioning
confidence: 99%